Eastern Germany ahead in employment of women - Elke Holst; Anna Wieber (DIW Economic Bulletin, 2014)
Almost a quarter of a century after the fall of the Wall, there are still more women in employment in eastern Germany than in the west. Although the disparity is marginal now, the two regions started from dramatically different levels. In 1991, immediately after reunification, the employment rate for women in western Germany was 54.6 percent, but since then it has increased year on year, reaching 67.5 percent in 2012. In eastern Germany, female employment initially plummeted after the fall of the Wall but then sharply increased again and, at 69.1 percent, slightly exceeded the western German rate in 2012. In both parts of the country, women are more likely to work part-time today than in the past, although, at 27.8 hours per week in 2013, the actual volume of work carried out by eastern German women is considerably higher than in the west (21.7 hours). According to a study conducted by DIW Berlin using Socio-Economic Panel (SOEP) study data, however, many women would prefer to work more hours per week. A comparison of the desired, contractually agreed, and actual weekly working hours of women in the east and west of the country shows that, on average, for eastern German women all values in these three categories far exceed even the maximum value for western German women. In contrast, the majority of employed men in both parts of the country would like to work a 40-hour week, but this is a reality for only 22.6 percent of western German and 29.2 percent of eastern German men. The majority works longer hours, despite the fact that this is unpopular among men. The post-reunification changes had a significant impact on the lifestyles of couples with children: the modernized breadwinner model (father in full-time work/mother part time) is playing an increasing role in both parts of Germany-in western Germany, this has been at the expense of the sole breadwinner model (father as sole earner) and, in the east, at the expense of the equality model (both parents working full-time).
Keywords: J12; J16; J21; J22; 330; labor supply; labor market participation; working time; working time preferences; East Germany; West Germany; modernized breadwinner model